1121 Single Use Nasal Endoscopes – A Review of The Cost and Organisational Implications Based on Department Size. (12th October 2021) - Wallace, J; Evans, V; Sanu, A; Howard, A; Berry, S
Abstract: Aim: Single use nasal endoscopes have become increasingly popular since the COVID-19 pandemic. By avoiding the risk of cross contamination and reducing exposure by eliminating the need for re-processing, the disposable scopes have clear safety benefits. Despite ENT UK guidelines recommending that disposable nasal endoscopes be available in every department for use in emergencies, they have often been considered prohibitively expensive. The aim of this study was to analyse the costs associated with traditional nasal endoscopes and compare them to the single use scopes. Method: A micro costing exercise was undertaken in three ENT departments: 2 university hospitals, and 1 district general hospital. The outcomes were compared and discussed with relation to the logistics of the departments, as well as organizational considerations. Results: Cost per procedure varied according to the reprocessing methods used in the different departments. The cost of the disposable nasal endoscopes appears high, however there are many hidden costs associated with the traditional scopes, which can be difficult to quantify accurately. Conclusions: Although disposable endoscopes appear costly, reprocessing and frequent repairs required for re-usable scopes account for the comparable cost per procedure. The high risk of COVID-19 transmission from examining the upper aerodigestive tract means that the safety benefits bear more weight in the current climate. However, concerns regarding environmental impact, image quality and storage of examinations also need to be considered.